Impact of Proficiency Testing on Results of the Microscopic Agglutination Test for Diagnosis of Leptospirosis - Chappel, R. J. (American Society for Microbiology, 2004)
A proficiency testing scheme for the leptospirosis microscopic agglutination test was provided to 37 laboratories in 23 countries in 2002 (round 1) and to 60 laboratories in 34 countries in 2003 (round 2). Thirty-four laboratories participated in both rounds. Each panel consisted of five rabbit serum samples, four of which were antisera raised against pathogenic serovars of Leptospira. One of these samples was a mixture of two different antisera. The rates of false-negative results, calculated on the basis of the assumption that serovars within a serogroup will cross-react, were 11% for round 1 and 14% for round 2. There were regional differences in the rates of false-negative results. The titers reported by laboratories testing for the same sample with the same serovar varied widely. Laboratories that had previously participated in round 1 reported fewer false-negative results in round 2 than new participants (10 and 21%, respectively [P = 0.002]) and reported 0.56 false-negative results per participant, whereas new participants reported 1.23 false-negative results per participant (P = 0.041). Laboratories that had previously participated also reported fewer false-negative results in round 2 than in round 1 when samples common to both rounds were tested (5 and 15%, respectively [P = 0.028]). The titers reported by the new participants were, on average, lower than those reported by the laboratories that had participated previously (P = 0.019) and were significantly more variable (P = 0.001). Analysis of these results suggests a positive impact of proficiency testing on the testing performance of the participating laboratories.